Septic Shock after Intracervical Laminaria Insertion - Shin-Yu Lin; Wen-Fang Cheng; Yi-Ning Su; Chi-An Chen; Chien-Nan Lee (Taiwanese Journal of Obstetrics & Gynecology, 2006)
Objective: Laminaria placement is seldom thought to be associated with postabortal sepsis Case Report: A nulliparous woman presented with high fever, low blood pressure, and signs of infection during artificial legal abortion with laminaria placement for cervical dilatation. Broad-spectrum antibiotics were given. Cultures of blood, placenta, and arterial line all yielded Enterobacter cloacae. The patient responded to antibiotics and supportive care. Conclusion: The use of laminaria still places patients at risk for infection because there is a certain risk of ascending colonization with potentially pathogenic microorganisms from the vaginal and cervical microflora, as in our patient. Surgical disinfection, prophylactic antibiotics, and shortened duration of laminaria placement are helpful to prevent infectious insult. Once signs of infection are noted, physicians should take action as soon as possible, such as initiating broad-spectrum antibiotics and intensive care.